Analisis Pengaruh Tingkat Pengangguran Terbuka dan Inflasi terhadap Kemiskinan di Kota Malang Tahun 2018-2023 - Tri Amukti, Fajar Dio Wahyu; Zagladi, Arief Noviarkahman (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze the effect of the Open Unemployment Rate (TPT) and inflation on poverty in Malang City in the period 2018–2023. The method used is quantitative research with multiple regression analysis. Secondary data was obtained from the Central Statistics Agency (BPS) and other related agencies, with the dependent variable being the poverty rate and the independent variables being TPT and inflation. The results of the study show that inflation has a significant effect on poverty with a regression coefficient of -0.145 and a significance value of 0.033, indicating that increasing inflation tends to reduce the poverty rate. Meanwhile, the TPT variable does not show a significant effect on poverty (p = 0.725). The regression analysis produces a coefficient of determination (R²) of 0.830, indicating that the independent variables are able to explain 83% of the variation in poverty. Although the regression model is significant at the 10% significance level (p = 0.070), it is not significant at the 5% level, so further analysis is needed to understand other factors that can affect poverty in Malang City. In addition, the results of the classical assumption test indicate that the model meets the assumption of normality and does not experience multicollinearity problems. Keywords: Poverty, Open Unemployment Rate, Inflation